The Effect of Ratio of Taro Flour, Taro Starch, and Wheat Flour with the Addition of CMC (Carboxyl Methyl Celulose) on the Chemical and Organoleptic Properties of Instant Noodles - Nursalimah Tinambunan; Herla Rusmarilin; Mimi Nurminah (Universitas Sumatera Utara, 2014)
This research was conducted to find out The effect of ratio of taro flour , taro starch, and wheat flour with the addition of CMC (carboxyl methyl celulose) on the quality of instant noodles, and to find out the chemical and organoleptic quality of instant noodles produced. This research used a completely raindomized design with two factors, they were: the ratio of composite flour (T); (80:0:20, 60:20:20, 40:40:20:20:60:20, 0:80:20) and concentration of CMC (C); (1%, 2%, and 3%). The parameters analyzed were moisture content, ash content, oxalate levels, water and oil absorption of the composite flour whereas on instant noodles were the ratio of taro flour, taro starch, and wheat flour with the addition of CMC, the parameters analyzed were moisture content, ash content, fat content, crude fiber content, protein content, loss of solids due to cooking, water absorption, percent elongation, total sugars,carbohydrate content, hedonic organoleptic test on color and flavour, and scores elasticity test of the instant noodles. The result of research showes that the ratio of taro flour, taro starch, and wheat flour gave highly significant effect on moisture content, ash content, oxalate levels, water and oil asorption on composite flour in resulting. The ratio of taro flour, taro starch, and wheat flour gave highly significant effect on moisture content, ash content, fat content, protein content, crude fiber content, loss of solids due to cooking, water absorption, total sugars, percent elongation, carbohydrate content, hedonic test on color and flavor, and elasticity scores test of the instant noodles. The concentration of CMC gave highly significant effect on moisture content, ash content, loss of solids due to cooking, protein content, crude fiber content, percent elongation, water absorption, hedonic test on flavour, and fat content of the instant noodles. The interaction of the two factors gave highly significant effect toward moisture content, ash content, fat content, water absorption, and loss of solids due to cooking. The ratio of taro flour, taro starch, and wheat flour (80:0:20) and concentration of CMC of 2% produced the best quality of instant noodles. Key words: Carboxyl Methyl Celulose, Instant Noodles, Taro Flour, Starch, Wheat